Autoantibodies in Spondyloarthritis, Focusing on Anti-CD74 Antibodies - Liu, Yuan; Liao, Xining; Shi, Guixiu (Frontiers in Immunology, 2019)
Spondyloarthritis (SpA) is an inflammatory rheumatic disease with diverse clinical presentation. The diagnosis of SpA remains a big challenge in daily clinical practice because of the limitation in specific biomarkers of SpA, more biomarkers are still needed for SpA diagnosis and disease activity monitoring. In the past, SpA was considered predominantly as auto-inflammatory disease vs. autoimmune disease. However, in recent years several researches demonstrated a broad autoantibody response in SpA patients. Study also indicated that mice lack of ZAP70 in T cell develop SpA featured inflammation. These studies indicated the autoimmune features of SpA and gave rise to the potential use of autoantibody in SpA management. In this article, we reviewed recent reports of autoantibodies associated with SpA patients, revealing the autoimmune features of SpA, suggesting the hypothesis that SpA was also an autoimmune disease, studies about the autoimmune features might provide more insights in the pathogenesis of SpA. In addition, as there are two opposite conclusions in the role of anti-CD74 autoantibody in the diagnosis of SpA, we also gave our own data on the diagnostic value of anti-CD74 in Chinese SpA patients. Though our data indicated that anti-CD74 might not be a good biomarker for SpA diagnosis in Asian people, CD74 was still a good molecule target in the research of SpA pathogenesis.